Advanced monitoring of South Portugal water bodies towards WFD - Martins, Flávio (2009)
The challenge on implementation of the EU Water Framework Directive (WFD) fosters the development of new monitoring methods and approaches. It is now commonly accepted that the use of classical monitoring campaigns in discrete point is not sufficient to fully assess and describe a water body. Due to this the WFD promote the use of modelling techniques in surface waters to assist all phases of the process, from characterisation and establishment of reference conditions to identification of pressures and assessment of impact. The work presented in this communication is based on these principles. A classical monitoring of the water status of the main transitional water bodies of Algarve (south of Portugal) is combined with advanced in situ water profiling and hydrodynamic, water quality and ecological modelling of the systems to build a complete description of its state. This approach extends spatially and temporally the resolution of the classical point sampling. The methodology was applied during a 12 month program in Ria Formosa coastal lagoon, the Guadiana estuary and the Arade estuary. The synoptic profiling uses an YSI 6600 EDS multi-parameter system attached to a boat and a GPS receiver to produce monthly synoptic maps of the systems. This data extends the discrete point sampling with laboratory analysis performed monthly in several points of each water body. The point sampling is used to calibrate the profiling system and to include variables, such as nutrients, not measured by the sensors. A total of 1427 samplings were performed for physical and chemical parameters, chlorophyll and microbiologic contamination in the water column. This data is used to drive the hydrodynamic, transport and ecological modules of the MOHID water modelling system (www.mohid.com), enabling an integrate description of the water column.